the Design of Pocket Books Based on Independent Curriculum as Teaching Materials in Diniyah Learning at Madrasah Ibtidaiyah - Khoirunnisa, Fita; Rofi'ah, Siti (BASICA Journal of Arts and Science in Primary Education, 2023)
Pocket books are print media that are small, light, can be stored in a pocket and are practical to carry and read anytime and anywhere. Pocket books can be used as supporting tools or complementary references that are used as a bridge for an educator in carrying out the learning process. This research aims to describe the process of developing a pocket book based on the independent plot at MI Islamiyah Jogoroto. This research uses a qualitative and quantitative approach, with descriptive data analysis. Data collection was carried out through interviews, questionnaires and documentation. The informants in this research consisted of the head of curriculum, head of student affairs, madrasa staff, class v students. Based on the results of the pocket book research, the results were very suitable for use with a percentage of expert validators of 96% and a percentage of student eligibility of 84.9%. With these results, this independent flow-based pocket book teaching material is categorized as very suitable and effective for use as pocket book teaching material for class V students of Madrasah Ibtidaiyah.